ENGAGING LEARNERS IN REAL LIFE COMMUNICATION. INTONATION PATTERNS IN QUESTIONS VS. STATEMENTS; STRESS ON CONTENT WORDS. (Multidisciplinary Journal of Science and Technology, 2025)
This article reviews current intonational research that is relevant to teaching and presents implications for pedagogy. It then argues that there are two primary reasons for a lack of innovation in intonation teaching materials. First, current materials are based on an inadequate view of the functions of intonation, especially in their overemphasis on its role in signaling grammatical relations and in their emphasis on its role in conveying speakers' attitudes and emotions.